Do the application forms and doses of boron affect wheat crops? - Galindo, Fernando S. [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Buzetti, Salatier [UNESP]; Boleta, Eduardo H. M. [UNESP]; Rodrigues, Willian L. [UNESP]; Rosa, Alexandre R. M. [UNESP] (Univ Federal Campina Grande, 2018)
Boron is one of the most limiting micronutrients in the grain production system in Brazil. 'thus, the objective of this study was to evaluate the effects of the application forms and doses of boron on the concentration of this nutrient in the leaves, straw, and grains of wheat, as well as the production components and grain yield. The residual effect of boron in the soil was also evaluated. An experiment was conducted in a no-tillage system in Oxisol with clay texture in Selviria, Mato Grosso do Sul. The experimental design was a randomized block design with four replicates arranged in a 4 x 3 factorial scheme. Four doses of boron (0, 1, 2, and 4 kg ha(-1)) were applied with a boric acid source (B = 17%) and three application forms: a) during the desiccation of the predecessor straw with herbicide; b) at the time of sowing in soil along with formulated fertilization seeding, and c) via the leaves with the application of post-emergent herbicide. The application of boron to the soil at the time of sowing at an approximate dose of 2 kg ha(-1) provides the highest number of spikelets per ear and wheat grain yield.
Keywords: Triticum aestivum; borated fertilization; boron time application; boron concentration in aerial part; grain yield